(untitled) (REVISTA NODO, 2023)
This article exposes the methodological process of creation in the realization of the software V.S.C.O (Video Synthesizer of Ocular Control), which is the product of the research-creation project of the same name that gathers evaluation results of its prototype by means of centered design tools. on the user (DCU). The user-software interface is also part of the conceptualization of a work of art that operates in the context of digital art and computational art. The descriptive methodology and mixed approach will allow, through the collection of user data, to delve into the public/player experience that integrates a type of game in the field of creation and entertainment, which allows to demonstrate in a perceptive evaluation of the digital work of art, of how it favors states of mental relaxation in the public. The link between the sound and the visual is also appreciated in the V.S.C.O’s computer system with the aesthetic and technical purposes of Visual Music, an aesthetic that dates back to the beginning of the 20th century and that was committed to the creation of a temporary architecture that is carried out in the synesthetic fusion of colors, shapes and movements. It is hoped that the visual and sound dynamics of the V.S.C.O, through its ability to interact with the public in the space, will build its own temporary architecture that links it to the technical and poetic aspects of Visual Music.